Bismuth‐Decorated Silicon Photocathodes for CO2‐to‐Formate Solar‐Driven Conversion. Issue 22 (16th September 2020) - Fu, Dong; Tourneur, Jeoffrey; Fabre, Bruno; Loget, Gabriel; Lou, Yaoyin; Geneste, Florence; Ababou‐Girard, Soraya; Mériadec, Cristelle
Abstract: The integration of metal‐based catalysts onto semiconducting electrodes provides a real benefit for the CO2 electrochemical conversion because it allows the electrochemical process to be activated by photogenerated electrons. In that context, we report here that silicon photocathodes modified with electrodeposited Bi nanostructures are highly active for the photoelectrocatalytic conversion of CO2 to formate. Through the consumed electrical charge and the electrodeposition time, it is possible to finely control both the structure and the density of the deposited catalyst. The optimal photocathode was prepared by using a 5 s electrodeposition time and exhibited the highest photocurrent density (−24.1 mA cm −2 ) with partial formate photocurrent density j formate =−17.4 mA cm −2 at −1.03 V vs Reversible Hydrogen Electrode (RHE), i. e. a 0.84 V overpotential for CO2 to formate conversion in CO2 ‐saturated 0.5 M KHCO3 solution. Such values highlight the excellent photoelectrocatalytic activity of our photocathodes. Abstract : CO2 Reduction : P‐type Si photocathodes functionalized with Bi catalyst were easily fabricated using a one‐step and fast electrodeposition method. A few seconds electrodeposition was sufficient for producing Bi‐decorated photocathodes showing the best electrocatalytic performance for the CO2 ‐to‐formate reduction characterized by a light‐limited photocurrent plateau of ∼24 mA cm −2 and a high Faradaic efficiency of >72 % for formate at ca. −1.0 V vs RHE.